2013
DOI: 10.1016/j.jcma.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

First drive-through pharmacy services in Taiwan

Abstract: The drive-through pharmacy provides patients with convenient access to pick up refilling prescriptions in a shorter time than ordinary pharmacy service. During a short-term follow-up, an overall increase in the prescription refilling rate was noted after the drive-through service was put into place. Our survey revealed that an upward of 90% of the patients were satisfied with the drive-through service. Future promotion of the service may help patients effectively utilize drive-through pharmacy prescription ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 7 publications
5
35
0
Order By: Relevance
“…In other countries, these services are usually called 'extended' services and are usually operated through private community pharmacies. [1][2][3][4] The heavily burdened public facilities fulfill prescriptions that was increasing steadily from 32 million in 2007 to 43.4 million in 2011 for a nation with a population of approximately 30 million inhabitants. This increasing trend of workload is a tremendous strain on time and resources that is pushing the limits of public pharmaceutical services as well as causing great distress to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, these services are usually called 'extended' services and are usually operated through private community pharmacies. [1][2][3][4] The heavily burdened public facilities fulfill prescriptions that was increasing steadily from 32 million in 2007 to 43.4 million in 2011 for a nation with a population of approximately 30 million inhabitants. This increasing trend of workload is a tremendous strain on time and resources that is pushing the limits of public pharmaceutical services as well as causing great distress to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, these services are usually called ‘extended’ services and are usually operated through private community pharmacies 1,2,3,4. The heavily burdened public facilities fulfill prescriptions that was increasing steadily from 32 million in 2007 to 43.4 million in 2011 for a nation with a population of approximately 30 million inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Taipei Medical University's affiliated Shuang Ho Hospital (SHH) implemented the first Taiwanese drive-through pharmacy service in July 2011 by opening a four-lane driveway near the hospital building. 7 It was found that the implementation of the SHH drive-through service generally increased the overall prescription refilling rate, online reservation usage and proportion of medications picked up in six months' period. As for Australia's much vaunted pharmaceutical services, available services include; One-stop-shop, forward dispensing, "Rolls Royce service", e-prescribing, chronic illness card, prescription reminder systems, drive through, pick up and home delivery services.…”
Section: Pharmacy Value Added Services From An International Perspectivementioning
confidence: 97%
“…Internationally, PVAS is provided by both private and public pharmacists. [7][8][9] The case in Malaysia is unique where government facilities are the sole and pioneering providers of PVAS by a large degree. Thus, higher PVAS adoption rates is a key ingredient in the national key results area (KRA) for healthcare delivery towards Malaysia's drive for a modern and efficient healthcare system.…”
Section: The Current State Of Pharmacy Value Added Services In Malaysiamentioning
confidence: 99%